Purpose-oriented reasoning in Hajj-related issues between tradition and contemporary reality: An analytical study of al-Wansharisi's fatwas in al-Mi'yar al-Mu'rib - Monia, El mohri; Messaouda, Allouache (Journal of Ecohumanism, 2026)
This study examines the maqāṣidī (higher objectives of Islamic law) dimension of contemporary Hajj-related legal issues through Al-Miʿyār al-Muʿrib wa al-Jāmiʿ al-Mughrib ʿan Fatāwā Ahl Ifrīqiyā wa al-Andalus wa al-Maghrib by Imam al-Wansharīsī. It aims to demonstrate the role of the higher objectives of Islamic law (Maqāṣid al-Sharīʿah) in shaping juristic reasoning concerning issues related to Hajj and ʿUmrah. The study adopts an inductive-analytical methodology by examining the Hajj-related legal cases documented in Al-Miʿyār al-Muʿrib and analyzing them in light of the theory of Maqāṣid al-Sharīʿah, while also relating them to selected contemporary issues concerning Hajj organization, crowd management, and public health measures.The study concludes that maqāṣid-oriented juristic reasoning played a fundamental role in the legal opinions of the jurists of the Maghrib and al-Andalus. In cases of conflict, the objectives of preserving religion, safeguarding human life, and maintaining public security were given precedence over certain individual interests associated with the performance of Hajj rituals. The findings further demonstrate that many contemporary issues—such as regulating the number of pilgrims, prohibiting the sale of Hajj visas, wearing face masks during iḥrām, and staying at ʿArafāt or outside Minā—can be understood and addressed within the framework of the universal objectives of Islamic law, particularly the preservation of life, the removal of hardship, and the realization of public order.